Constitutive over-expression of rice ClpD1 protein enhances tolerance to salt and desiccation stresses in transgenic Arabidopsis plants. (September 2016) - Mishra, Ratnesh Chandra; Richa,; Grover, Anil
Highlights: Rice ClpD1 gene forms several transcript variants with distinct expressions. ClpD1.3 protein exhibits ATP-dependent chaperone activity. Transgenic plants overexpressing ClpD1.3 were tolerant to osmotic stress. Proline content and starch breakdown were higher in transgenic plants. Abstract: Caseinolytic proteases (Clps) perform the important role of removing protein aggregates from cells, which can otherwise prove to be highly toxic. ClpD system is a two-component protease complex composed of a regulatory ATPase module ClpD and a proteolytic component ClpP. Under desiccation stress condition, rice ClpD1 ( OsClpD1 ) gene encoding for the regulatory subunit, was represented by four variant transcripts differing mainly in the expanse of their N-terminal amino acids. These transcripts were expressed in a differential manner in response to salt, mannitol and polyethylene glycol stresses in rice. Purified OsClpD1.3 protein exhibited intrinsic chaperone activity, shown using citrate synthase as substrate. Arabidopsis (Col-0) plants over-expressing OsClpD1.3 open reading frame downstream to CaMV35S promoter (ClpD1.3 plants) showed higher tolerance to salt and desiccation stresses as compared to wild type plants. ClpD1.3 seedlings also showed enhanced growth during the early stages of seed germination under unstressed, control conditions. The free proline levels and starch breakdown activities were higher in the ClpD1.3 seedlings as compared to the wild type Arabidopsis seedlings. It thus emerges that increasing the potential of ClpD1 chaperoning activity may be of advantage in protection against abiotic stresses.